2020
DOI: 10.1051/epjap/2020200063
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid nanophotonic-nanomagnonic SiC-YiG quantum sensor: II/dark spins quantum sensing with V2 spins and fiber based OP-PELDOR/ODMR

Abstract: First experiments like optically detected (OD) electron paramagnetic resonance (ODMR), photoluminescence detected RABI oscillations, and optical pumping (OP) assisted pulsed EPR measurements of T2 and T1 of V2 spins in bulk SiC, which were previously demonstrated on various home build EPR spectrometers with free space optics, are here all demonstrated for the first time using a commercial X band pulsed EPR spectrometer combined with a single optical fiber and a standard external photoluminescence setup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…13 This study confirmed the feasability of creating very shallow silicon vacancies near the surface, but no information about their intrinsic quantum spin coherence properties, depurated from inhomogeneous effects and ensemble effects, could be obtained, such that we cannot conclude whether this approach is detrimental or not to their usefull intrinsic quantum spin coherence properties. This is in good agreement with their well know spin hamiltonian: 1,2,4…”
Section: Experiments and Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…13 This study confirmed the feasability of creating very shallow silicon vacancies near the surface, but no information about their intrinsic quantum spin coherence properties, depurated from inhomogeneous effects and ensemble effects, could be obtained, such that we cannot conclude whether this approach is detrimental or not to their usefull intrinsic quantum spin coherence properties. This is in good agreement with their well know spin hamiltonian: 1,2,4…”
Section: Experiments and Resultssupporting
confidence: 90%
“…See also cited references. 4,7,8 vacancies defects created by this implantation. This was for example demonstrated for the creation of arrays of silicon vacancies color centers at <z>= 42 nm, with a longitudinal straggling of 35 nm, using 30 keV C + ions implantation in SiC.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations